Representation of Single Father in the Movie Fatherhood - Cateline Marscha; Fanny Lesmana (Jurnal Spektrum Komunikasi, 2022)
Film is one of the media that is still often used by many people to convey a message and have an impact on a wide audience who enjoy it. One of them is the depiction of a person in a film that gives a message of its impression to the audience. Since the Covid-19 pandemic that entered Indonesia in March 2021, many people have died due to exposure to the virus. Not infrequently, some people have also lost their parents during this pandemic, such as losing their mothers and leaving fathers with their children. The phenomenon of single fathers and their stories of defending their families and raising their children eventually became the main attraction for the audience. At the same time, a film called Fatherhood was released which tells the story of a single father and his daughter. The author conducted this research because it was deemed to describe how a single father faces the problems that surround him. The purpose of this study was to find out the message of the single father representation conveyed in the media of this film. The method used is Roland Barthes' semiotics. Semiotics Roland Barthes will discuss from 3 points of view, namely denotation, connotation, and also myth. In this study, the theory used is about single-parent problems, Roland Barthes' semiotics, and also films. The findings in this study are that every single father will face several problems such as work, child care, economy, and also social pressure.